Stiffness comparison of mushroom and straight SS and TMA lingual archwires - Luca Lombardo; Antonella Carlucci; Mario Palone; Francesco Mollica; Giuseppe Siciliani (SpringerOpen, 2016)
Abstract Background The aim of this study is to investigate the relative stiffness of straight and mushroom lingual archwires of different diameters, cross sections and alloys, plotting their load/deflection graphs and using a modified three-point bending test. Methods Fujita's mushroom archwires and straight lingual archwires of different diameters, cross sections and alloys were derived by a virtual set-up of an equal malocclusion and were cut at their straight distal portion. These distal portions were tested using a modified three-point bending test by an Instron 4467 dynamometer and the forces, were exerted at 1-mm deflection and were compared on each resulting load/deflection curve by means of ANOVA (p < 0.05). Results All upper lingual mushroom wires exerted significantly lower forces than the straight wire. Lower mushroom archwires were stiffer than their upper counterparts, which were longer and featured inset bends. In the lower arch, similar levels of forces were recorded for the two types of wire. Load-deflection curves were higher for the straight wires, and stiffness increased proportionally with their diameter. Conclusions The stiffness of an archwire is a function of its diameter, length and the alloy it is made from. In lower lingual wires, there is little difference in stiffness between mushroom and straight wires, but in upper wires, the straight version is considerably stiffer. The greater bearing effect exhibited by the straight wire in the working and finishing phases makes it less susceptible to bowing effect and therefore preferable for sliding mechanics during en masse retraction, particularly in the upper arch.